A narrow-band speckle-free light source via random Raman lasing. Issue 1 (2nd January 2016) - Hokr, Brett H.; Schmidt, Morgan S.; Bixler, Joel N.; Dyer, Phillip N.; Noojin, Gary D.; Redding, Brandon; Thomas, Robert J.; Rockwell, Benjamin A.; Cao, Hui; Yakovlev, Vladislav V.; Scully, Marlan O.
Abstract : Currently, no light source exists which is both narrowband and speckle free with sufficient brightness for full-field imaging applications. Light-emitting diodes are excellent spatially incoherent sources, but are tens of nanometers broad. Lasers, on the other hand, can produce very narrow-band light, but suffer from high spatial coherence which leads to speckle patterns, which distort the image. Here, we propose the use of random Raman laser emission as a new kind of light source capable of providing short-pulsed narrow-band speckle-free illumination for imaging applications.